2014
DOI: 10.1155/2014/649816
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Moss-Dominated Crusts andArtemisia ordosicaon Wind Erosion and Soil Moisture in Mu Us Sandland, China

Abstract: To better understand the effects of biological soil crusts (BSCs) on soil moisture and wind erosion and study the necessity and feasibility of disturbance of BSCs in the Mu Us sandland, the effects of four treatments, including moss-dominated crusts alone, Artemisia ordosica alone, bare sand, and Artemisia ordosica combined with moss-dominated crusts, on rainwater infiltration, soil moisture, and annual wind erosion were observed. The major results are as follows. (1) The development of moss-dominated crusts e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…First, shrubs create significant ‘islands of fertility’, which could improve soil properties and facilitate vegetation recovery by controlling desertification processes (Zhao et al ., ). Second, shrubs are highly tolerant to moderate burial, denudation and drought in semi‐arid regions (Li et al ., ), and they have great wind erosion resistance (Yang et al ., ) because of their dense branches significantly decreasing near‐surface wind speed (Guo, ). Third, shrubs have an important role in maintaining or augmenting herbaceous species richness in semi‐arid regions (Zhao et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, shrubs create significant ‘islands of fertility’, which could improve soil properties and facilitate vegetation recovery by controlling desertification processes (Zhao et al ., ). Second, shrubs are highly tolerant to moderate burial, denudation and drought in semi‐arid regions (Li et al ., ), and they have great wind erosion resistance (Yang et al ., ) because of their dense branches significantly decreasing near‐surface wind speed (Guo, ). Third, shrubs have an important role in maintaining or augmenting herbaceous species richness in semi‐arid regions (Zhao et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that BSCs were sensitive to disturbance (Ponzetti and McCune, ); the cover, abundance and composition of BSCs were all affected by disturbance (Warren and Eldridge, ), and improper disturbance would aggravate the occurrence of desertification (Mario and Navar, ; Ponzetti and McCune, ). However, the stable and high coverage of A. ordosica communities, which has a great ability to protect soil from wind erosion (Yang et al ., ), has formed in semi‐fixed and fixed sand dunes in the Mu Us Sandland (Xiong et al ., ). BSCs are commonly found in A. ordosica communities and are growing with increasing plant cover (Zhang et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the positive roles played by dew and fog are also an increase in the relative water content of the leaves (Gouvre & Grammatikopoulos, 2003), branches (Hill et al, 2015;Yates & Hutley, 1995), and the xylem water potential (Berry & Smith, 2013;Kim & Lee, 2011), all of which assist in chlorophyll and carotenoid recovery . Additionally, dew and fog may reduce wilting and increase survival probabilities during water stress (Babu & Went, 1978;Cosh et al, 2009;Duvdevani, 1957), improve the recovery of DNA damage of seeds (Gutterman & Shem-Tov, 1997;Yang, Zhang, Dong, Boubriak, & Huang, 2011;Zhuang & Zhao, 2016) and germination (Yang et al, 2011;Yang, Bu, Mu, Shao, & Zhang, 2014;Zhuang & Zhao, 2016), and increase plant growth, yield, and biomass (Boucher et al, 1995;Duvdevani, 1957;Duvdevani, Reichert, & Palti, 1946;Zhuang & Ratcliffe, 2012). Although some researchers report on dew utilization by roots (Pan et al, 2010) or on the use of vapour absorption by roots (Kosmas et al, 2001;Ramírez, Bellot, Domingo, & Blasco, 2007), these claims were not yet substantiated and require further research.…”
Section: The Effects Of Nrw On Plants Snails and Insectsmentioning
confidence: 99%
“…Xiong et al (2011) determined that the disturbance on welldeveloped BSCs could lead to greater infiltration depth after rainfall which would be very important for the growth and regeneration of deep-rooted shrubs. Moreover, our earlier research has demonstrated that moderate disturbances to well-developed BSCs didn't result in rapidly increased wind erosion when the shrub's coverage reached approximately 50 % (Yang et al 2014). A factor offsetting the disturbance of BSCs is that the fragmentation of the BSCs caused by disturbance would be partially compensated by an increase of newly formed BSCs (Hiernaux et al 1999).…”
Section: Discussionmentioning
confidence: 99%